2023
DOI: 10.1038/s41419-023-05706-2
|View full text |Cite
|
Sign up to set email alerts
|

USP7- and PRMT5-dependent G3BP2 stabilization drives de novo lipogenesis and tumorigenesis of HNSC

Abstract: GTPase-activating protein-binding protein 2 (G3BP2) is a key stress granule-associated RNA-binding protein responsible for the formation of stress granules (SGs). Hyperactivation of G3BP2 is associated with various pathological conditions, especially cancers. Emerging evidence indicates that post-translational modifications (PTMs) play critical roles in gene transcription, integrate metabolism and immune surveillance. However, how PTMs directly regulate G3BP2 activity is lacking. Here, our analyses identify a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…USP7 regulates the function and turnover of a wide range of substrates, including P53, ERK1/2, PD-L1, PRMT5, ANXA1, STAT3 and ECT2, which are crucial components of numerous oncogenic signalling pathways. [46][47][48][49][50][51][52] For example, USP7 is a crucial deubiquitinase needed to stabilise oncogenic versions of DDX3X. By stabilising DDX3X, USP7 increases Wnt/beta-catenin signalling, which has previously been demonstrated to be strongly correlated with colorectal cancer cell invasiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…USP7 regulates the function and turnover of a wide range of substrates, including P53, ERK1/2, PD-L1, PRMT5, ANXA1, STAT3 and ECT2, which are crucial components of numerous oncogenic signalling pathways. [46][47][48][49][50][51][52] For example, USP7 is a crucial deubiquitinase needed to stabilise oncogenic versions of DDX3X. By stabilising DDX3X, USP7 increases Wnt/beta-catenin signalling, which has previously been demonstrated to be strongly correlated with colorectal cancer cell invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Deubiquitylases have been implicated with a number of cancers, including HCC, according to recent research. USP7 regulates the function and turnover of a wide range of substrates, including P53, ERK1/2, PD‐L1, PRMT5, ANXA1, STAT3 and ECT2, which are crucial components of numerous oncogenic signalling pathways 46–52 . For example, USP7 is a crucial deubiquitinase needed to stabilise oncogenic versions of DDX3X.…”
Section: Discussionmentioning
confidence: 99%
“…G3BP2 was first identified as an androgen-responsive gene, core components that contributes to stress granules (SGs) assembly and RNA metabolism [ 38 ]. Increased G3BP2 promoted the growth of cancer cells and high expression level of G3BP2 was associated with poor prognostic in Head and Neck squamous cell carcinoma, prostate cancer, breast, and lung cancer [ 39 42 ]. However, we found that the high expression level G3BP2 was associated with better prognostic in ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“… 179 In prostate cancer, research has revealed that G3BP1 interacts with USP7 and PRMT5, contributing to the stabilization of G3BP2 and influencing its ubiquitination status. 180 This in turn affects the functionality of deacetylase SIRT1, ultimately impacting the activity of downstream transcription factors like NF-κB and β-catenin, culminating in an increase in de novo lipid synthesis, thus enhancing the malignancy and drug resistance of the tumor.…”
Section: Molecular Functions Of Stress Granules In Cancer Biologymentioning
confidence: 99%